Social Support Networks, Coping Mechanisms, and Mental Health Outcomes in Post-Traumatic Stress Disorder (PTSD) Patients in Yogyakarta - Wahidin Wahidin; Sabil Mokodenseho (The Eastasouth Journal of Social Science and Humanities, 2023)
In Yogyakarta, Indonesia, this study examines the complex interactions that exist between coping strategies, social support networks, and mental health outcomes in people with Post-Traumatic Stress Disorder (PTSD). The study uses regression and correlation analysis on a broad sample to determine the links between coping techniques, perceived social support, and the severity of PTSD symptoms. In line with previous research, the results emphasize the protective value of emotional support and proactive social support-seeking. But the surprising positive relationship that was found between avoidance and the severity of symptoms presents a fresh angle that calls for more research on the cultural dynamics of coping strategies. This study establishes the foundation for further research on PTSD in the particular sociocultural environment of Yogyakarta and offers subtle insights for customized therapies.